2014 IEEE 64th Electronic Components and Technology Conference (ECTC) 2014
DOI: 10.1109/ectc.2014.6897498
|View full text |Cite
|
Sign up to set email alerts
|

Ag alloy wire characteristic and benefits

Abstract: Gold wire has been high volume production in IC packaging industry. With soaring price of gold in recent years and IC packaging search for cost reduction, 2nd alternative for wire bonding type assembly. But copper wire has drawbacks in control issues such as pad crack, aluminum splash, cratering and low throughput, Cu wire need a more complex multi-processing program problems, even if copper raw material cost is low, the process costs are increased These limitations of copper wire thickness and structure. Silv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Fine pitch Cu wire bonding reliability is proven in manufacturing process [7]. Good reliability results are also obtained in Ag alloy wire [8] although there is much less HVM and reliability data with Ag alloy comparing to Cu wire.…”
Section: Wire Type Comparisonmentioning
confidence: 99%
“…Fine pitch Cu wire bonding reliability is proven in manufacturing process [7]. Good reliability results are also obtained in Ag alloy wire [8] although there is much less HVM and reliability data with Ag alloy comparing to Cu wire.…”
Section: Wire Type Comparisonmentioning
confidence: 99%
“…In choosing a wire material, one important thing to consider is how it bonds to the Al pads [12,13]. Several research works have shown that the bonding on the Ag-Al interface is caused by intermetallic compound (IMC) formation [14][15][16]. Based on the Ag-Al phase diagrams [17,18] and experiment results, the main IMCs are Abstract Typical epoxy molding compounds (EMC) contain chlorine ions that cause silver wire-bond failures under highly accelerated temperature/humidity stress test (HAST).…”
Section: Introductionmentioning
confidence: 99%
“…Ag 3 Al and Ag 2 Al [15][16][17][18]. Reliability of Ag alloy wirebonds has been evaluated under high temperature and high humidity test conditions [11,[13][14][15][16]. In high temperature storage test (HTS), Ag alloy wire-bonds pass industrial reliability standard [11,14,15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Die crack, Al-pad peeling and internal dielectric crack are the most common challenges for those applications. In this case, silver (Ag) and Ag-alloy wires emerge as other alternatives since they have similar properties like wire hardness, elongation and breaking load at room temperature as Au wire while having a more competitive price [1,2,3].…”
Section: Introductionmentioning
confidence: 99%